Molecular identification and phylogenetic assessment of species under genus Parapenaeopsis Alcock, 1901, from Indian waters. (17th February 2019) - Chowdhury, L. Mog; A, Kathirvelpandian; PR, Divya; VS, Basheer; Shanis, Rajool; Chelath, Mohitha; Pavan-Kumar, A.; Krishna, Gopal
Abstract: Genus Parapenaeopsis constitute an important fishery resource in Indian waters. Parapenaeopsis stylifera, being morphologically very similar to Parapenaeopsis coromandelica, mainly differentiated using telsonic armature and it is subject of controversy regarding the number of armature for the species. The present study was aimed to resolve the taxonomic ambiguity between P. stylifera and P. coromandelica and to study phylogenetic relationship among five species under the genus Parapenaeopsis using partial sequences of mitochondrial 16S ribosomal DNA (rDNA) and cytochrome c oxidase subunit I (COI) genes. Sequence analysis revealed an average genetic divergence value ranging from 7.65 to 20.3% for COI gene and 2.4 to 12.0% for 16S rDNA gene between five species under study. The result shows that P. stylifera and P. coromandelica Alcock, 1906 are genetically a distinct species with average divergence value of 7.6% based on COI sequence and 2.4% based on the 16S rDNA. However, systematic relationship between the P. stylifera and P. coromandelica were closer than other species, thus formed separate clade in phylogenetic tree. The species specific molecular signatures developed in the present study will be helpful in effective fisheries management of the species in Indian waters.